Therapeutic and pharmacological aspects of photodynamic product chlorophyllin - Divya Chaturvedi; Kavita Singh; Vinay Kumar Singh (European Journal of Biological Research, 2019)
Medicinal plants have been used for thousands of years to flavor and conserve food, to treat health disorders and to prevent diseases including epidemics. They can provide biologically active molecules and lead structures for development of modified derivatives with enhanced activity or reduced activity.  The isolation and identification of active principles and elucidation of the mechanism of action of a drug is of paramount importance. One such compound is chlorophyllin, a water soluble analogue of the ubiquitous green pigment chlorophyll. It acts as an effective inhibitor of aflatoxin hepatocarcinogenesis in animal models by blocking carcinogen bioavailability. Further anti-cancer effects of chlorophyllin including antioxidant activity, inhibition of enzymatic activity that converts inert procarcinogens into active carcinogens, stimulation of enzymatic activity that promotes the elimination of toxic substances from the body and antitumor activity have likewise been evidenced by controlled studies. Phytotherapy of snails by photodynamic chlorophyllin is a new approach to control the epidemic fasciolosis. Photosensitive chlorophyllin is degraded very fast without the formation of toxic byproducts, therefore, it is environmentally sound and economically safe also.